Formulation of Red Beet (Beta vulgaris. L) and Aloe Vera (Aloe vera) Gel Extracts as Anti-Aging - Lestari, Mutiara Dwi; Maimunah, Siti; Prayoga, Andre (JURNAL PEMBELAJARAN DAN BIOLOGI NUKLEUS, 2023)
Anti-Aging can prevent or slow down the effects of skin aging. This study aims to formulate extracts of beetroot (Beta vulgaris. L) and Aloe Vera (Aloe Vera) in gel preparations and test their anti-aging effectiveness. This research was conducted at the Laboratory of Pharmaceutical Chemistry, University of Sari Mutiara Indonesia. The tools used are skin analyzer and moisture checker. B. vulgaris Samples from Brastagi, Karo Regency and A.vera taken from Rantauprapat, Labuhan Batu Regency. Methods of implementation Beet extraction was extracted with 96% ethanol solvent, andÂ A.vera extract from the juicer. The irritation test on 12 volunteers used nettle extract cream with the highest concentration of 0.5%. Anti-aging activity testing used 12 female volunteers aged 19-22 years, who were divided into 4 groups, namely 3 volunteers (A; Blank), administration of beetroot extract gel (B. vulgaris. L) andÂ A.vera (B) : 3%), (C: 6%), and (D: 9%). 3. Parameters measured include moisture content, number of pores and wrinkles. Data distribution was analyzed using the One sample Kolmonogrov-Smirnov Test method. Then proceed with the analysis of the One-Way Anova method. The results of research on beet (B. vulgaris. L) and Aloe Vera (A.vera) gel preparations can be formulated in a gel dosage form. pH 6.9, W/O emulsion type, viscosity 2500-3500 cps, non-irritating, and stable on storage for 28 days. Beet fruit extract (B. vulgaris) and aloe vera viscous extract (A.vera) can be formulated in the form of an anti-aging gel that can provide an anti-aging effect at the best concentration, namely at a concentration of 9% by increasing skin moisture to 40.24%; smaller pores 0.53%; and reduce wrinkles by 0.33%